Why has canine rabies remained endemic in the Kilosa district of Tanzania? Lessons learnt and the way forward - Kipanyula, M. J. (Infect Dis Poverty, 2015)
BACKGROUND: Domestic dogs are the main targets for rabies control as they are the principal reservoir for transmission of the rabies virus to humans and other domestic animals. The purpose of this study was to identify the factors that contribute to the rabies virus infecting the human population in a rural community of Eastern Tanzania. METHODS: Using a cross-sectional study design, field visits were conducted to gather information on villagers’ knowledge on and practices associated with canine rabies control and dog vaccination campaigns. RESULTS: A total of 248 individuals were interviewed in the Kilosa district, Tanzania. Almost two-thirds (61.3 %) had a primary school education. The majority (91.1 %) of the respondents were aware that rabies is acquired through dog bites and 66.9 % knew about the clinical signs of rabies in an animal. Very few (17.7 %), however, were aware of the clinical signs of rabies in humans. Only 20.4 % of the respondents knew how rabies is controlled in dogs and 71 % were not aware of dog vaccination campaigns. The average number of dogs kept per household was 4 ± 3.3; 70.0 % of the respondents had one to five dogs, 28.3 % had six to dog dogs, and 1.6 % had 16–20 dogs. The dogs were primarily used to guard livestock and property, and to hunt. About 59.7 % of the respondents indicated that rabies was a public health problem. Low vaccination coverage was observed in the study area, with previous mass vaccination campaigns covering only 24.4 % of the dog population. Dogs appeared to have limited value in the studied community. Furthermore, there were no proper waste disposal facilities and oftentimes wild canids and felids visited the villages to scavenge on kitchen leftovers. CONCLUSION: Although communities in the Kilosa district had knowledge on rabies in dogs, they were not aware of the public health implication of the disease, which thus led a poor response during mass dog vaccination campaigns. Establishment of a well-coordinated rabies control program, strategic public health awareness campaigns, and active and passive surveillance systems for humans and domestic and wild animals should be considered as strategies to control and eradicate rabies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40249-015-0085-6) contains supplementary material, which is available to authorized users.